Non-alcoholic Steatohepatitis (NASH) Drug Discovery - Building a Consensus on ADME Screening Tools and Clinical Pharmacology Strategies to Aid Candidate Development - Ranjeet Prasad Dash; R. Jayachandra Babu; Nuggehally R Srinivas (Frontiers Media S.A., 2018)
Number of drugs with different mechanisms of actions is undergoing clinical trials for non-alcoholic steatohepatitis (NASH). Given the complexity of the disease with respect to pathophysiology in the liver and associated changes in the renal function, it becomes apparent that a clear ADME (absorption, distribution, metabolism and excretion) strategy needs to be put in place for a successful nomination of a drug candidate for NASH. This review discusses using in vitro and in vivo ADME screens to understand the properties of drugs and to establish whether or not the chosen drug(s) can overcome the challenges related hepatic and renal transporters covering both uptake and efflux mechanisms imposed by NASH. A complete panel of in vivo preclinical experiments including a 14C-labeled study are proposed in NASH animal models to delineate the problematic areas for early drug development. Furthermore, a framework is provided with respect to the clinical pharmacology studies early in clinical development to characterise in an unbiased manner, the altered pharmacokinetics of drug in NASH patients for optimizing the dose selection for late phase clinical development. Because NASH patients have other co-morbid conditions and are prescribed co-medications for treating blood pressure, type 2 diabetes mellitus, obesity, dyslipidemia and many more disorders, it is also suggested to examine the drug-drug interaction potential by performing a cocktail probe study to cover a broad range of cytochrome P450 (CYP) enzymes and transporters.